Anthropology for dummies - Smith, Cameron McPherson, 1967-; Davies, Evan Tyler Suliëman (Wiley, 2008)
"Explains the fundamentals of biological and cultural anthropology and tips on how to find a career in anthropology."
Obsahuje rejstřík
Keywords: antropologie; antropologie -- metodologie; kulturní antropologie; biologická antropologie; anthropology; anthropology -- methodology; cultural anthropology; biological anthropology; příručky; handbooks, manuals, etc